Posttraumatic stress disorder in women : experiences form the psychiatric clinic, University Hospital Center Zagreb, Croatia - Jovanović, Nikolina, liječnica (Array, 2009)
Abstract: Posttraumatic stress disorder (PTSD) is an anxiety disorder that develops after a severe traumatic event or experience. Lifetime prevalence rate in the European population is 1.9 % and it is higher for women (2.9%) then for men (0.9 %). The aim of this study was to examine rates and sociodemographic and clinical characteristics of women with PTSD who were hospitalized at the Psychiatric clinic of University Hospital Center in Croatia over the years 1990–2007. Data were gathered retrospectively from the medical charts. We found that 67 women were diagnosed with PTSD which is 0.58% of all admissions over these years. Majority suffered from comorbid depression (N=51) and various somatic conditions, especially malignant gynecological tumors (N=23). No significant differences were found in distribution of PTSD symptoms in relation to the combat vs. civilian trauma. We found that patients with combat trauma often suffer from comorbid depression, while those with civilian traumas more often reported somatic conditions, especially malignant gynecological tumors. Our institution is a speciality clinic at a tertiary care medical center which tends to accumulate patients with serious forms of the disorder, and therefore our results can not be generalized to other settings involved in working with women with PTSD. Our results indicate that psychiatrists’ assessment of female patients should inevitably include lifetime traumatic experiences, and among those with PTSD, special attention should be paid to comorbid depression and malignant tumors